Bisphenol A Increases the Migration and Invasion of Triple‐Negative Breast Cancer Cells via Oestrogen‐related Receptor Gamma. Issue 4 (29th April 2016) - Zhang, Xiao‐Lin; Liu, Na; Weng, Shan‐Fan; Wang, Hong‐Sheng
Abstract: Triple‐negative breast cancer (TNBC) is characterized by great metastasis and invasion capability. Our study revealed that nanomolar bisphenol A (BPA), one of the most ubiquitous endocrine disruptors, can increase wound closure and invasion of both MDA‐MB‐231 and BT‐549 cells. BPA treatment can increase protein and mRNA expression of matrix metalloproteinase‐2 (MMP‐2) and MMP‐9, while had no effect on the expression of vimentin (Vim) and fibronectin (FN) in TNBC cells. The expression of G‐protein‐coupled receptor (GPER), which has been suggested to mediate rapid oestrogenic signals, was not varied in BPA‐treated MDA‐MB‐231 and BT‐549 cells. Its inhibitor G15 also had no effect on BPA‐induced MMPs expression and cell invasion. Interestingly, BPA treatment can significantly increase the mRNA and protein expressions of oestrogen‐related receptor γ (ERRγ), but not ERRα or ERRβ, in both MDA‐MB‐231 and BT‐549 cells. The knock‐down of ERRγ can markedly attenuate BPA‐induced expression of MMP‐2 and MMP‐9 in TNBC cells. BPA treatment can activate both ERK1/2 and Akt in TNBC cells. Both inhibitors of ERK1/2 (PD98059) and Akt (LY294002) can attenuate BPA‐induced ERRγ expression and cell invasion of MDA‐MB‐231 cells. Collectively, our data revealed that BPA can increase the expression of MMPs and in vitro motility of TNBC cells via ERRγ. Both activation of ERK1/2 and Akt participated in this process. Our study suggests that more attention should be paid to the roles of xenoestrogens such as BPA in the development and progression of TNBC.